Traveling Salesman Problem for optimizing the promotion of medical devices in Pekanbaru city hospital - Pandu Pratama Putra; Dafwen Toresa (International Journal of Data Science, Computer Science and Informatics Technology (InJODACSIT), 2021)
Travel from one place or location to place others taking into account the path or route the shortest one to go through in the case of traveling can be solved by the ant algorithm method. With the limited number of sales and efficiency in the medical equipment sales job, it is not uncommon for workers to do this experiencing various problems in the visited clients at the hospital, one of them the simple problem that is experienced is a problem time and cost efficiency in traveling. Not to mention the added limitations of the company's budget and time. and workers wish to visit multiple locations all at once. These time and cost efficiency issues are frequent happens because you don't know which path to go they traveled by selecting the best route by sales employees can at least minimize costs expenses for transportation and time wasted on Street. And the number of places you want to visit at various locations with different mileage make a decision which location want to go to. Ants algorithm find the most optimal path of all probability of the path the ant has taken with leaving pheromones in excess a lot. compared to paths that are not optimal. Result research shows that the optimal pathway with most pheromones are location route paths the shortest and optimum hospital.